Peningkatan Kesadaran Nelayan Sawapudo Tentang Penangkapan Ikan Ramah Lingkungan - Indrayani, Indrayani; Tadjuda, Muslim; Arami, Hasnia; Alimina, Naslina; Mustafa, Ahmad; Abdullah, Abdullah; Kamri, Syamsul; Sudarno, Sudarno; Muhammad Irsan, La Ode (Jurnal Gema Ngabdi, 2025)
Sawapudo Village fishermen will benefit from this community service project because it will increase their awareness of fishing techniques that are less harmful to the environment. There is a lack of awareness among fishermen regarding the consequences of utilizing fishing gear that is harmful to the marine ecosystem, which is why this training is so crucial. Some of the methods that are utilized include lectures, hands-on field practice, and interactive and interactive conversations. Twenty fishermen participated in this exercise, which was carried out in conjunction with the administration of the community. The findings of the evaluation indicate that the participants have a better comprehension of the significance of marine conservation, the selection of fishing gear that is responsible for the environment, and the support of government rules that are associated with the management of sustainable fisheries populations. Through the use of participative and educational methods, this exercise demonstrates that the mentality of fishermen can be changed to become more responsible and sustainable in their fishing practices. Because of this, it is strongly suggested that training of this kind be maintained and carried out in other coastal locations that have features that are equivalent to those of the current area.